Fungsi Pengarahan Kepala Ruangan Meningkatkan Pelaksanaan Serah Terima Antar Shift - Eva Riyani; Enie Novieastari; Hanny Handiyani; Sarvita Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to improve the implementation of the handover between shifts through the direction of the head of the room such as motivation, communication, delegation and supervision in two maternity wards consisting of one room head and fifteen nursing staff. The study was conducted for five weeks at X Hospital with data obtained through interviews, observations and surveys. The method used is a case study through problem analysis using a fishbone diagram and then making innovative changes using Lewin's 3-step model approach. Implementation is carried out for one week at the time of handing over the morning shift. The results showed that the program was still in the movement stage, the handover time was adequate according to Standard Operating Procedures, the head of the room supervised two wards alternately, surveys of nursing staff related to the function of directing the head of the room increased by 6.7%. In conclusion, the implementation of the briefing function carried out by the head of the room in the handover process between shifts in the two maternity rooms of X Hospital has increased based on the results of the questionnaire distributed to the nursing staff. The results of the implementation of supervision show that the time required in the handover process is more adequate and in accordance with the existing SPO. The recommendation is that the hospital needs to continue this program to the next stage, the nursing sub-services need to make regulations on nursing handover guidelines and carry out tiered supervision in the wards. Keywords: Directional function, head of room, maternity ward, handover